Composition of Gut Microbiota of Children and Adolescents With Perinatal Human Immunodeficiency Virus Infection Taking Antiretroviral Therapy in Zimbabwe. (24th September 2019) - Flygel, Trym T; Sovershaeva, Evgeniya; Claassen-Weitz, Shantelle; Hjerde, Erik; Mwaikono, Kilaza S; Odland, Jon Ø; Ferrand, Rashida A; Mchugh, Grace; Gutteberg, Tore J; Nicol, Mark P; Cavanagh, Jorunn P; Flægstad, Trond
Abstract: Background: Human immunodeficiency virus (HIV) infection causes impairment of the gastrointestinal barrier, with substantial depletion of CD4 + T cells in the gut. Antiretroviral therapy (ART) restores CD4 + counts and may have beneficial effects on gut microbiota in adults. Little is known about effect of long-term ART on gut microbiome in HIV-infected children. We investigated composition of gut microbiota in HIV-infected and -uninfected children and assessed associations between gut microbiota and patient characteristics. Methods: In a cross-sectional study, rectal swabs were collected from 177 HIV-infected and 103 HIV-uninfected controls. Gut microbial composition was explored using 16S ribosomal ribonucleic acid sequencing. Results: Human immunodeficiency virus-infected children had significantly lower alpha-diversity and higher beta-diversity compared to HIV-uninfected. No association was observed between microbiome diversity and CD4 + T-cell count, HIV viral load, or HIV-associated chronic lung disease. We found enriched levels of Corynebacterium ( P < .01), Finegoldia ( P < .01), and Anaerococcus ( P < .01) in HIV-infected participants and enrichment of Enterobacteriaceae ( P = .02) in participants with low CD4 + counts (<400 cells/mm 3 ). Prolonged ART-treatment (≥10 years) was significantly associated with a richer gut microbiota by alpha diversity. Conclusions: Human immunodeficiency virus-infected children have altered gut microbiota. Prolonged ART may restore the richness of the microbiota closer to that of HIV-uninfected children. Abstract : HIV-infected African children and adolescents have altered gut microbiota compared to HIV uninfected. ART was significantly associated with a higher alpha diversity, and prolonged ART may restore richness of the microbiota closer to that of HIV-uninfected children.